That's not Metastatic Thyroid Cancer: Patterns of Non-malignant Radioiodine Uptake - Daniella F Pinho (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2017)
Radioactive Iodine (RAI) has been an integral part of the identification, surveillance, and treatment of the most common types of metastatic thyroid carcinoma since its first use in 1941. However, false positive uptake of RAI on whole body scintigraphy scans in tissues other than in metastatic disease is frequently observed. This article presents a case series of relatively uncommon situations of RAI uptake which could be mistaken for malignant uptake. Cases were divided into categories based on uptake mechanism: metabolic, physiologic, mechanism: metabolic, physiologic, inflammatory, and contamination.